Discrete strategies to reduce intake of discretionary food choices: a scoping review. Issue 1 (December 2016) - Grieger, Jessica; Wycherley, Thomas; Johnson, Brittany; Golley, Rebecca
Abstract On a population level, dietary improvement strategies have had limited success in preventing the surge in overweight and obesity or reducing risk factors for chronic disease. While numerous multi-component studies have examined whole-of-diet strategies, and single component (i.e. discrete) dietary intervention strategies have targeted an increase in core foods (e.g. fruits, vegetables, dairy), there is a paucity of evidence on the effectiveness of dietary intervention strategies targeting a decrease in discretionary choices. The aim of this review was to identify dietary intervention strategies that are potentially relevant to reducing intake of discretionary choices in 2–65 year olds. A scoping review was carried out to map the literature on key discrete dietary intervention strategies that are potentially applicable to reducing discretionary choices, and to identify the targeted health/nutrition effects (e.g. improve nutrient intake, decrease sugar intake, and reduce body weight) of these strategies. Studies conducted in participants aged 2–65 years and published in English by July 20, 2015, were located through electronic searches including the Cochrane Library, Medline, Embase, CINAHL, and Scopus. Three thousand two hundred and eighty three studies were identified from the search, of which 44 met the selection criteria. The dietary intervention strategies included reformulation (n  = 13), substitution (n  = 5), restriction/elimination (n  = 9), supplementation (n  = 13), and nutrition education/messages (n  = 4). The key findings of the review were: restricting portion size was consistently beneficial for reducing energy intake in the acute setting; reformulating foods from higher fat to lower fat could be useful to reduce saturated fat intake; substituting discretionary choices for high fibre snacks, fruit, or low/no-calorie beverages may be an effective strategy for reducing energy intake; supplementing nutrient dense foods such as nuts and wholegrain cereals supports an improved overall diet quality; and, a combination of permissive and restrictive nutrition messages may effectively modify behavior to reduce discretionary choices intake. Longer-term, well-controlled studies are required to assess the effectiveness of the identified dietary strategies as interventions to reduce discretionary choices intake.